Promising approaches of cataract treatment in patients with primary open-angle glaucoma - I.E. Ioshin; A.I. Tolchinskaya; A.V. Rakova; E.A. Berezenko (Офтальмохирургия)
Purpose. To evaluate a two-stage approach to surgical treatment of patients with cataract and primary open-angle glaucoma based on micropulse transscleral cyclophotocoagulation (MP-TSCPC) and phacoemulsification. Material and methods. The results of surgical treatment of 34 patients with cataract and primary open-angle glaucoma with non-dispersed intraocular pressure (IOP) were analyzed. A safer sequential surgery was chosen: at the first stage, MP-TSCPC was performed, at the second – cataract phacoemulsification. Results. After MP-TSCPC, the hypotensive effect was achieved in all 34 patients: IOP at the moderate stage was 14.6±1,4 mm Hg, at the advanced stage – 15.8±2,2 mm Hg. 1 month after surgery. Carrying out the second stage – phacoemulsification of cataracts 2–4 weeks after MP-TSCPC allowed to avoid reactive hypertension and achieve high functional results. IOP from the first day was 13.8±1,0 mm Hg in patients with moderate stage and 14.9±3,1 mm Hg in patients with advanced stage and remained compensated for 3 months after surgery. Visual acuity 3 months after surgery was 0.85±0.05 in patients with moderate and 0.73±0.05 with advanced stage. Anti-inflammatory prevention based on 0.1% fluorometholone acetate solution, considering the minimal effect on the IOP of the operated eye, showed promising advantages over other glucocorticoids for patients with glaucoma and cataracts. Conclusion. Sequential surgery with MP-TSCPC at the first stage and following phacoemulsification (against the background of stabilized IOP) is characterized by high functional results and minimal risk of complications in patients with comorbid pathology. Anti-inflammatory prevention based on 0.1% fluorometholone acetate solution, considering the minimal effect on IOP of the operated eye, has promising advantages for patients with glaucoma and cataracts.